Лунный замок - Андрианова-Голицына Ирина Анатольевна (Детский детектив, 2002)
Экземпляры: ДБ; ф6 (20221123) / Инвентарный номер: 37938 / Цена: 20.00 / Сис.шифр: Р2ср / Авт.знак: А 65 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6